SENSITIVITY AND REPEATABILITY OF THE KNEE TORQUE AND ANGLE ACTIVE TRACKING TASKS - Nejc Šarabon; Jernej Rošker; Miloš Kalc (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2010)
The aim of our study was to test sensitivity and repeatability of torque and angle active tracking tasks at the knee joint and to compare the results of these two tests with one another. Twenty-four healthy young volunteers participated in the study (age 23.2 ± 2.16 years). Each subject performed two active tracking tasks: knee torque tracking task (KTT) and knee angle tracking task (KAT) - three 60-second repetitions each task. The reference signal which the subject tried to follow via visual feedback was a cyclically repeating sinusoidal curve (0.25 Hz cycle frequency) with the normalized amplitude (10-90 % active range of motion for KAT and 30-60 % maximal voluntary torque for KTT). For both, KAT and KTT, low repeatability was observed for a single repetition test design, while the repeatability increases to reasonably good when using the three repetitions average as a measure (intra-class correlation coefficient 0.822 and 0.806 for KAT and KTT, respectively). The presence of statistically significant differences (t-test, p < 0.001) and the low correlation determination (R2 = 0.137) between KAT and KTT suggests that these two tests measure two separate sensory-motor skills and rely on different underlying sensory sub-systems. We strongly believe that the active tracking methods can become a useful tool for sensory-motor function assessment in clinical and research work. However, in order to gain the best possible metric characteristics of these methods and to diminish the learning effect, additional research efforts are needed.